2008
DOI: 10.1093/ijlct/3.4.254
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a solar assisted micro-cogeneration ORC system

Abstract: In this work, three solar assisted thermodynamic cycles for a micro-cogeneration system with a power output of 5 kW are studied. The thermodynamic cycles are based on the Organic Rankine Cycle (ORC) and the operating temperatures of solar thermal collectors are 80°C, 100°C-150°C and 200°-250°C, for cycles 1, 2 and 3, respectively. The main work objective was to model the selected cycles for optimisation according to the temperature range. The performance of several fluids was evaluated from a thermal and an ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Based on the numerical simulations carried out, they reported that the system overall efficiency is directly proportional to the CO 2 flow rate and inversely proportional to the solar collector area. A similar study was conducted by Facao et al [37] examining a 5 kWe solar driven micro-CHP system with an organic Rankine cycle. They reported that the system electrical generation efficiency is directly proportional to the temperature output from the solar collector and can attain 22% at 230°C working fluid temperature.…”
Section: Expander Selectionmentioning
confidence: 80%
See 1 more Smart Citation
“…Based on the numerical simulations carried out, they reported that the system overall efficiency is directly proportional to the CO 2 flow rate and inversely proportional to the solar collector area. A similar study was conducted by Facao et al [37] examining a 5 kWe solar driven micro-CHP system with an organic Rankine cycle. They reported that the system electrical generation efficiency is directly proportional to the temperature output from the solar collector and can attain 22% at 230°C working fluid temperature.…”
Section: Expander Selectionmentioning
confidence: 80%
“…A similar study was conducted by Facao et al . examining a 5 kWe solar driven micro‐CHP system with an organic Rankine cycle. They reported that the system electrical generation efficiency is directly proportional to the temperature output from the solar collector and can attain 22% at 230°C working fluid temperature.…”
Section: Expander Selectionmentioning
confidence: 99%
“…Facao et al [54] proposed a thermal analysis of three different solar-driven ORC systems for micro-CHP with a maximum power output of 5 kW. By comparing different climatic conditions leading to a range of operating conditions of the solar thermal collectors between 80 °C and 250 °C, the maximum electricity generation efficiency was 22.2%.…”
Section: Micro-chp Orc-based Systemsmentioning
confidence: 99%
“…The plant design chosen for investigation uses flat plate solar collectors combined with a gas burner, as described by Facao et al (2008). Recent works on small-scale solar cogeneration ORCs using scroll expanders present encouraging estimations of the dynamic performance (Twomey et al, 2013;Ziviani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%